On modules over integer-valued group rings of locally soluble groups with rank restrictions imposed on subgroups - Dashkova, O. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We study the ZG-module A such that Z is the ring of integers, the group G has infinite section p-rank (or infinite 0-rank), C_G(A) = 1, A is not a minimax Z-module, and, for every proper subgroup H of infinite section p-rank (or infinite 0-rank, respectively), the quotient module A/C_A(H) is a minimax Z-module. It is proved that if the group G under consideration is locally solvable, then G is a solvable group. Some properties of a solvable group of this type are obtained.